Community Economic Empowerment Model Based on Local Wisdom in the Perspective of Maslahah (A Case Study of the Red-and-White Crackers Business in Panyabungan) - Madinah, Futri; Rokan, Mustafa Kamal; Nasution, Juliana (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study aims to examine a community-based economic empowerment model rooted in local wisdom, using a case study of the Red and White Crackers business in Banjar Kobun Village, Panyabungan District, Mandailing Natal Regency. This enterprise not only serves as the primary source of livelihood for the local community but also reflects cultural values and local traditions. The research method employed is descriptive qualitative, utilizing in-depth interviews with 20 business actors and one key informant for further analysis. Data were analyzed using thematic analysis techniques to identify key patterns related to forms of economic empowerment and local wisdom values. The findings reveal that the Red and White Crackers business significantly improves community welfare, reduces unemployment rates, and strengthens local cultural identity. The identified empowerment model is participatory, prioritizes the principle of maslahah (public interest), and opens opportunities for development through marketing digitalization, strengthening local institutions, and cross-sector collaboration. However, while the descriptive qualitative method provides a rich narrative, the absence of comparative analysis limits the generalizability of the findings. This study could be strengthened by integrating data from other similar communities to assess whether the empowerment model can be widely adopted or remains unique to this specific context. The study concludes that community-based economic empowerment rooted in local wisdom is an effective strategy for creating sustainable and inclusive economic development and has the potential to be replicated in other regions with similar cultural characteristics.